“Diseño de una metodología para la localización de infraestructura peatonal para personas en condición de discapacidad.” (2020)
This research will be aimed at examining and evaluating the existing pedestrian infrastructure for people with disabilities through accessibility and connectivity measures and evaluating the different topological, measurement and urban variables. The aim is to propose policies that favor walking conditions for people with disabilities, evaluating the consequences that may be exerted on them. For the development of this research, the necessary information was collected to know the state of the roads, which helps us to correctly evaluate the walking conditions in the city of Barranquilla to establish a walking index for people in disability conditions. The roads studied were chosen for their pedestrian flow and for their high level of shopping and entertainment, basing on measurements to obtain the results of said index. The application of this will help us to establish recommendations on pedestrian infrastructure, recognize if these places should be intervened to improve the quality of life of people with disabilities in search of inclusive transport